Pemberdayaan Kader Posyandu Upaya Deteksi Dini Komplikasi Kehamilan Penggunakan Community Screening Card Pada Ibu Hamil di Desa Penfui Timur Kabupaten Kupang - Namsyah Baso; Serlyansie V. Boimau; Yurissetiowati (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2024)
One of the causes of maternal mortality is undetected high-risk pregnancies. Since the Covid-19 pandemic, motherhood classes in Kupang Regency have been postponed. By carrying out routine and regular Antenatal Care (ANC) through examination of the condition of the mother and fetus, you can detect any risks that may arise during pregnancy. So that pregnancy complications can be recognized by cadres and pregnant women, it is necessary to train cadres in self-screening for pregnancy complications. One effort that can be done is by using a Community Screening Card. The aim of this activity is to empower posyandu cadres in carrying out early pregnancy detection using the Community Screening Card. The community service method uses steps: counseling, cadre training, demonstrations/simulations using Community Screening Cards directly to pregnant women. and mentoring. This activity requires the activeness of pregnant women and midwives in the mentoring process using a community screening card (consultation with a midwife). The results of the activity showed that there was an increase in understanding after the training was held, namely that training participants who had a good level of understanding increased from 0% to 85%. Of the total participants, there were still 15% who understood quite well. Conclusion: increasing the role of health cadres in early detection and referral efforts for maternal and child health cases, especially in cases of referral for childbirth in the context of preparedness and preparedness for complications for mothers and newborns, is expected to reduce maternal and child mortality rates.